Produksi Siratro (Macroptilium Atropurpureum) Bermikoriza Di Tanah Pasca Penambangan Batubara - Taufan Purwokusumaning Daru; Roosena Yusuf (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
The purpose of this study was to determine the production of siratro that inoculated with AMF through coating techniques then planted in overburden soil compared with top soil . The experiment was conducted in a polybag size of 10 kg. The results showed that the top soil fertility status used in this study was high content of C organic and phosphorus (P) , while the overburden soil (OB) was low, where a low content of C organic and P were very low. Shoot dry matter production of siratro seeds planted with AMF inoculated in the top soil was highest, while that was not coated with AMF was lower, but higher than the seed planted in OB soil. The average uptake of nitrogen and phosphorus have the same pattern, in which the seeds were planted in the form of AMF coating seed in top soil has a higher uptake, followed by AMF seed and non-AMF seed that planted in OB soil. The percentage of AMF colonization in the roots of siratro was no effect on dry matter production, N and P uptake